Conceptual Analysis Of Total Productive Maintenance (TPM) And Reliability Centered Maintenance (RCM) - Ab Azid, Nor Azianti (Universiti Sains Malaysia, 2018)
Maintenance is an important issue that needs to be addressed during the design and manufacturing or building of a system. A good maintenance strategy will increase the performance of the company. Total Productive Maintenance (TPM) is one of the famous maintenance strategies that are widely used within the organization. One maintenance strategy used by the organization which is a Reliability Centered Maintenance (RCM). Both TPM and RCM have its own concepts and principles as a maintenance strategy to give impact to the performance and reliability of the system. Therefore, in this research, the TPM will be studied with RCM to show their relationship. Based on the conceptual analysis, the author will analyze publications from journals, books, and articles to find all related information, such as genealogy, definition, concepts, and principle, and implementation. The conceptual method used is Näsi's four elements of conceptual analysis. This research also used a questionnaire survey method. The objective of this survey is to study the current maintenance strategies in the real industries and to relate it to TPM and RCM. The survey has been answered through electronically and the survey is done using the application of Google Forms. At the end of this research, the result of the study of TPM and RCM shows that TPM started in 1970 while RCM started in the 1960s, but the foundation of TPM and RCM was started in 1950s with Breakdown Maintenance (BM). TPM basically is about elimination faults through day-to-day activities involving the entire force work while the concept of RCM is to improve equipment reliability. The objective of TPM is to achieve zero breakdowns, zero defects, and zero accidents while TPM is to preserve the functions. Although both using different tools both are linked together through the Lean tool. TPM mostly can be implemented in big plant industries while RCM can be applied in small or medium size plant. Both can increase product quality, equipment reliability, increase safety, and increase profit. From the survey result, most of the respondent comes from the companies that implementing tradisional maintenance (PM and CM) rather than TPM and RCM.